Confidence Intervals for the Variance and the Ratio of Variances of Log-Normal Distribution with Known Coefficients of Variation - Niwitpong, Sa-aat (IJRDO -JOURNAL OF MATHEMATICS, 2016)
This paper presents the confidence interval for the variance and the ratio of variances of lognormal distribution with known coefficients of variation. We derived analytic expressions to find the coverage probability and the expected length of the proposed confidence interval.